2D materials coated on etched optical fibers as humidity sensor - Erfan Owji (Nature Portfolio, 2021)
Abstract In this investigation, etched-fibers are coated by 2D layers such as Molybdenum disulfide (MoS2), Molybdenum diselenide (MoSe2) and composition of graphene and graphene oxide (G/GO) to modify humidity sensing. The relative differentiation of attenuations (RDA) in presence of relative humidity (RH) is measured by Optical Loss Test Set at two standard-wavelengths-telecommunication (1310 nm and 1550 nm). Results show that the etched single-mode fiber (ESMF) coated with G/GO has relatively high and one by one function for RDA versus RH (more than 30%). Also, its sensitivity and variance are reasonable. The MoSe2 based sensor is applicable at humidity below 30% because of higher RDA. However, it is not useful at humidity more than 30% due to the absence of one by one function for RDA versus RH. Besides, ESMF coated with MoS2 has indistinctive behavior and is not useful as a humidity sensor.